Biodeterioration of canvas paintings: microbial role and development of sustainable treatments for biocontrol - Giovanna Climaco; Gianmaria Oliva; Paola Fiore; Consiglia Tedesco; Stefano Castiglione; Giovanni Vigliotta (Applied Microbiology and Biotechnology)
Abstract Biodeterioration of paintings, caused by microorganisms interacting with the organic/inorganic compounds of the canvas, represents a serious problem for preserving cultural heritage. In our study, the microbial degradation caused on an eighteenth century painting “Sant’Anna, San Gioacchino e la Vergine Bambina” was investigated. Seventeen bacterial and six fungal strains on the altered parts of the canvas were identified, and their deteriorating ability were evaluated on two pictorial pigments: the yellow ochre and the ivory black. We recognized that microorganisms interacted with these pigments and modified their chromatic features. Furthermore, we adopted an eco-friendly antimicrobial treatment based on natural plant extracts (thymus, rosemary, and garlic) as an alternative to conventional biocides and highlighted how rosemary (Salvia rosmarinus) extract was the best and inhibited 74% of the isolated bacterial strains. When the extract was applied on the contaminated canvas, it reduced bacterial colonization by ~ 75% in only 48 h and eliminated the fungi within 7 days. The extract application was optimized, to minimize potential alterations of the painting caused by the extract, by adopting different strategies: (i) direct nebulization, (ii) Evolon® tissue (an innovative technical polyester-polyamide textile), and (iii) pretreatment with cyclomethicone D5. Finally, we also verified that it did not cause chromatic variations on the canvas confirming its suitability for conservation purposes. Our study provides new insights on the role of microorganisms in the deterioration of cultural heritage and highlights the potentiality of plant-based antimicrobials as sustainable, non-invasive, and alternative to traditional methods for the artwork preservation. Future research should focus on long-term efficacy assessments and formulation optimization to enhance applicability in heritage conservation practices. Key points • Identification of 17 bacteria and 6 fungi from a deteriorate canvas painting • Microorganisms altered yellow ochre and ivory black, causing chromatic changes • Rosemary extract applied on canvas reduced microbial colonization